Dual-wavelength thulium ytterbium Co-doped fiber laser - Haris, Hazlihan; Muhammad, Ahmad Razif; Saidin, Norazlina; Zainal Abidin, Mohd. Shahnan; Arof, Hamzah; Paul, Mukul Chandra; Harun, Sulaiman Wadi (Institute of Advanced Engineering and Science (IAES), 2017)
We report on the generation of dual-wavelength fiber laser peaking at 1990.64 and 1998.92 nm with a simple ring cavity setup. The lasers are demonstrated using a fabricated silica-based nanoengineered octagonal shaped double-clad Thulium-Ytterbium co-doped fiber (TYDF) as a gain medium in a simple all-fiber ring configuration. By using 980 nm multimode laser, a stable dual-wavelength laser is generated at a threshold pump power of 1500 mW due to the non-polarization rotation (NPR) effect occurred in the cavity. The effect has been self-controlled by a suppression of mode competition in the gain medium. The result shows that the slope efficiency of the generated dual–wavelength laser is measured to be 27.23%. This dual-wavelength TYDF laser operated steadily at room temperature with a 34 dB optical signal-to-noise ratio